A estação do neolítico antigo da Encosta de Sant’Ana (Lisboa): resultados das campanhas de escavação de 2004 a 2006 - Leitão, Vasco (2021)
The results of the excavations carried out between 2004 and 2006 at the Encosta de Sant´ Ana located in the Historic Center of Lisbon are presented. The formation of the respective stratigraphic sequence was characterized and all the collected remains were thoroughly studied, analyzing the respective distribution among the excavated areas and their potential relationship with the identified archaeological structures. The absolute chronology was determined by two radiocarbon AMS analysis, which situate this occupation in the Early evolved Neolithic in the transition from the 6th to the 5th millennium BC, allowed the establishment of comparisons with several sites of similar chronology, located in the region surrounding the Tagus estuary. For the archaeological structures identified; for the safe stratigraphy that made it possible to consider the recovered remains as constituting complete and closed sets, of great importance both in diversity and in the number of artefacts; and also due to the absolute chronology strictly determined by two AMS dating of bone samples from the terrestrial biosphere, the Encosta de Sant’ Ana site assumes itself as one of the most relevant sites of the Early Neolithic published so far in Portuguese territory.